Capital social y desarrollo rural sostenible: revisión desde el terreno - Cruz Maceín, José Luis; Casals, Gilles (Revista Española de Desarrollo y Cooperación, 2023)
The concept or paradigm of social capital has been one of the last incorporations into development theory, and its relevance to fight against poverty it´s being more and more recognized. The present article makes a review of some of the contents of social capital and applies it to the experience of an ONGD (Fundacio’n IPADE) in the Natural Area of National Integrated Handling - Apolobamba. The conclusion of the analysis emphasizes the relevance to foster the social capital, beyond the community and the frame of poverty-ethnic group, to build a solid and lasting social capital that contributes to a sustainable rural development.